2017
DOI: 10.1099/jmm.0.000449
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Mycobacterium tuberculosis and rifampicin resistance in extrapulmonary tuberculosis and sputum smear-negative pulmonary suspects using Xpert MTB/RIF

Abstract: The Xpert MTB/RIF assay is a rapid and simple technique with high sensitivity and specificity for diagnosing TB and detecting drug resistance in extrapulmonary and smear-negative TB cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
5
29
1
Order By: Relevance
“…The results of our study are comparable to those a recent meta-analysis which reported the pooled sensitivity of Xpert in smear positive-culture positive PTB as 98%, and a sensitivity was 67% and specificity 99% for smear negative TB. [17] The results for the sensitivity of the Xpert MTB/RIF assay are also consistent with previous studies conducted in neighbouring countries; a study conducted in Pakistan by Ullah et al (2017), [18] who reported a sensitivity of 80.0%; in Korea by Lee [20,21,22] The Xpert MTB/RIF assay simultaneously identifies MTB and detects rifampicin resistance with molecular beacons to detect five overlapping 81-bp regions in the rpoB gene known as the rifampicin resistance determining region. [23] It has been shown that 95% of all rifampicin-resistant MTB strains contain mutations in the region of the rpoB gene.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study are comparable to those a recent meta-analysis which reported the pooled sensitivity of Xpert in smear positive-culture positive PTB as 98%, and a sensitivity was 67% and specificity 99% for smear negative TB. [17] The results for the sensitivity of the Xpert MTB/RIF assay are also consistent with previous studies conducted in neighbouring countries; a study conducted in Pakistan by Ullah et al (2017), [18] who reported a sensitivity of 80.0%; in Korea by Lee [20,21,22] The Xpert MTB/RIF assay simultaneously identifies MTB and detects rifampicin resistance with molecular beacons to detect five overlapping 81-bp regions in the rpoB gene known as the rifampicin resistance determining region. [23] It has been shown that 95% of all rifampicin-resistant MTB strains contain mutations in the region of the rpoB gene.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, high sensitivity values were obtained with GX-Ultra in a large variety of extrapulmonary samples, and the results were superior to those of previous studies that applied Xpert MTB/RIF to similar specimens. The improvement was especially notable for lymph nodes, whose sensitivity increased between 17.1 and 23.5% more with GX-Ultra than with its predecessor (9,(18)(19)(20). Similarly, the nonsterile fluids obtained sensitivity values 15.7 to 27% higher with the novel assay than with Xpert MTB/RIF (9,19,20); in the case of tissue samples, the increase was 20 to 44.9% larger with the GX-Ultra (9,19).…”
Section: Discussionmentioning
confidence: 93%
“…In comparison with the other commercially available NAATs, it is based on a fully-automated process (Theron et al, 2013;Le Palud et al, 2014;Boehme et al, 2010;World Health Organization, 2011;Sharma et al, 2015;Albert et al, 2016). Its diagnostic accuracy was widely confirmed on sputum specimens; however, in recent years its performance was successfully assessed on bronchoscopic specimens such as BW (Le Palud et al, 2014;Barnard et al, 2015;Lee et al, 2013;Ko et al, 2016;Sharma et al, 2015;Jo et al, 2016), BAL (Theron et al, 2013;Mok et al, 2016;Le Palud et al, 2014;Lee et al, 2013;Ko et al, 2016;Agrawal et al, 2016;Khalil and Butt, 2015;Sharma et al, 2015;Ullah et al, 2017), and endobronchial ultrasound guidedtransbronchial needle aspiration (EBUS-TBNA) (Dhasmana et al, 2014;Dhooria et al, 2016a;Lee et al, 2017) (Table 1).…”
Section: Bronchoalveolar Lavage and Bronchial Washing Aspiratementioning
confidence: 99%